Survival and Home Range Estimates of Pen-Raised Northern Bobwhites in Buffer Strip and Non-Buffer Strip Habitats - Michael J. Oakley; Dixie L. Bounds; Theodore A. Mullet; Karen D. Gruen (National Quail Symposium Proceedings, 2017)
We investigated the effect of agricultural buffer strips on survival and home range estimates of pen-raised northern bobwhites (Colinus virginianus) at Tudor Farms on the Eastern Shore of Maryland. In September 2000 we released groups of bobwhites into 9 buffer strip (treatment) areas and 9 non-buffer strip (control) areas among 11 agricultural farms. Each group consisted of 4 radiomarked bobwhites and 26 non-radiomarked bobwhites. To maintain contact with the established coveys, additional radiomarked bobwhites (n = 177) were introduced into the coveys as radiomarked birds died. Survival for bobwhites released in buffer strip areas was lower (P < 0.001) than survival in non-buffer strip areas. None of the radiomarked bobwhites released in the buffer strip areas survived past 27 weeks, whereas 11% of radiomarked bobwhites in non-buffer strip areas survived to 27 weeks and 1 bird survived to 41 weeks. Predation was the primary mortality factor (88%), followed by unknown causes (7%), stress (2%), hunting (2%), and road kill (1%). Mean fall and winter home range (95% minimum convex polygon) for 21 bobwhite coveys was 24.2 +- 3.5 ha, ranging from 1.7 to 65.8 ha. Home range areas of bobwhite coveys in buffer strips (n = 12, x¯ +- 15.0 2.7 ha) was significantly smaller (P = 0.002) than non-buffer strip coveys (n = 9, x¯ = 36.4 +- 4.9 ha). We conclude that the smaller home ranges in buffer strip areas seem to indicate better habitat quality; however, high mortality rates of pen-raised bobwhites limited our ability to confirm this.
Keywords: buffer strips; Colinus virginianus; habitat analysis; home range; Maryland; mortality; northern bobwhite; radiotelemetry; survival